2021
DOI: 10.1038/s41467-021-24208-3
|View full text |Cite
|
Sign up to set email alerts
|

High thermoelectric figure of merit of porous Si nanowires from 300 to 700 K

Abstract: Thermoelectrics operating at high temperature can cost-effectively convert waste heat and compete with other zero-carbon technologies. Among different high-temperature thermoelectrics materials, silicon nanowires possess the combined attributes of cost effectiveness and mature manufacturing infrastructures. Despite significant breakthroughs in silicon nanowires based thermoelectrics for waste heat conversion, the figure of merit (ZT) or operating temperature has remained low. Here, we report the synthesis of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 42 publications
0
30
1
Order By: Relevance
“…And these fibers do not require using ion milling/etching as reported for nanowires to cleave surface oxides and measure TE properties. 29,36 Beyond these, we carry out a bending procedure and consecutively measure I-V characteristics of the representative BTF and BSTF (fiber diameter D~4 µm) by applying two gold-plated tungsten probes (Figure 4g and Supplementary Figure S7).…”
Section: Measured Room-temperature Thermoelectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…And these fibers do not require using ion milling/etching as reported for nanowires to cleave surface oxides and measure TE properties. 29,36 Beyond these, we carry out a bending procedure and consecutively measure I-V characteristics of the representative BTF and BSTF (fiber diameter D~4 µm) by applying two gold-plated tungsten probes (Figure 4g and Supplementary Figure S7).…”
Section: Measured Room-temperature Thermoelectric Propertiesmentioning
confidence: 99%
“…And these fibers do not require using ion milling/etching as reported for nanowires to cleave surface oxides and measure TE properties. [29,41] Beyond these, we carry out a bending procedure and consecutively measure I-V characteristics of the representative BTF and BSTF (fiber diameter D ≈ 4 µm) by applying two gold-plated tungsten probes and silver paste (Figure 4g; Figure S10, Supporting Information). Using the original resistance R 0 as a reference, the bending-state resistance R is normalized to exhibit a change of the electrical resistance as a function of 0.05-5 mm bending radius r (Figure 4h).…”
Section: Measured Room-temperature Thermoelectric Propertiesmentioning
confidence: 99%
“…The use of porous SiC is encouraged owing to its excellent high temperature thermomechanical strength and thermal shock resistance 15,170–172 . It has been reported that a thermoelectric material with low electrical resistivity, low thermal conductivity, and high Seebeck coefficient provides an overall high figure of merit and power factor, which correspond to a high thermoelectric efficiency 43,173–175 . Controlled electrical and thermal conductivities 28,31,33,43 along with the semiconducting nature (both n‐ and p‐type) of porous SiC make it a promising candidate for application in high temperature thermoelectric energy generators.…”
Section: Applications Of Porous Sic With Controlled Electrical Resist...mentioning
confidence: 99%
“…15,[170][171][172] It has been reported that a thermoelectric material with low electrical resistivity, low thermal conductivity, and high Seebeck coefficient provides an overall high figure of merit and power factor, which correspond to a high thermoelectric efficiency. 43,[173][174][175] Controlled electrical and thermal conductivities 28,31,33,43 along with the semiconducting nature (both n-and ptype) of porous SiC make it a promising candidate for application in high temperature thermoelectric energy generators. Figure 11 summarises the research work carried out to evaluate the thermoelectric performance of porous SiC.…”
Section: Thermoelectric Conversionmentioning
confidence: 99%
“…It is worth noting that recently, the hydraulic diameter, four times the reciprocal of the S/V, which is more consistent with the size effect, has been adopted to characterize the size of non-circular nanowires, including quasi-1D van der Waals crystal nanowires obtained from liquid exfoliation method, [85][86][87] Ag nanowires with pentagonal cross section, 51 and porous Si nanowires. 88 In addition to silicon nanowires, the thermal conductivities of various nanowires of other materials have been measured and in general, a significant reduction from the bulk value as a result of the classical size effect has been observed. 20,21,[89][90][91][92] Again, for studies with varying diameters, the imposed boundary scattering at different levels served as variable "boundary conditions" helping to elucidate the phonon transport mechanisms in these nanowires.…”
Section: The Classical Size Effect For Phononsmentioning
confidence: 99%